Mitochondrial genome characterization of the family Trigonidiidae (Orthoptera) reveals novel structural features and nad1 transcript ends - Ma, Chuan (Sci Rep, 2019)
The Trigonidiidae, a family of crickets, comprises 981 valid species with only one mitochondrial genome (mitogenome) sequenced to date. To explore mitogenome features of Trigonidiidae, six mitogenomes from its two subfamilies (Nemobiinae and Trigonidiinae) were determined. Two types of gene rearrangements involving a trnN-trnS1-trnE inversion and a trnV shuffling were shared by Trigonidiidae. A long intergenic spacer was observed between trnQ and trnM in Trigonidiinae (210−369 bp) and Nemobiinae (80–216 bp), which was capable of forming extensive stem-loop secondary structures in Trigonidiinae but not in Nemobiinae. The anticodon of trnS1 was TCT in Trigonidiinae, rather than GCT in Nemobiinae and other related subfamilies. There was no overlap between nad4 and nad4l in Dianemobius, as opposed to a conserved 7-bp overlap commonly found in insects. Furthermore, combined comparative analysis and transcript verification revealed that nad1 transcripts ended with a U, corresponding to the T immediately preceding a conserved motif GAGAC in the superfamily Grylloidea, plus poly-A tails. The resultant UAA served as a stop codon for species lacking full stop codons upstream of the motif. Our findings gain novel understanding of mitogenome structural diversity and provide insight into accurate mitogenome annotation.